Validasi Instrumen Eksplorasi Etnomatematika pada Museum Kandil Kemilau Emas Di Pulau Belimbing 1 - Dermawan, Agus; Zulfah, Zulfah; Astuti, Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to determine the validity of the instrument to be used in ethnomathematics exploratory research at the Kandil Kemilau Emas Museum on Belimbing Island 1. The subjects in this study consisted of 3 validators who are experts in their fields. This interview sheet can be used as a research need because it has been validated by three validators who are experts in their fields. Based on the validator's assessment of the interview instrument, it is in the valid category.